2007
DOI: 10.1111/j.1464-410x.2007.07117.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes using a fourth‐generation lithotripter: a new benchmark for comparison?

Abstract: OBJECTIVE To evaluate the efficacy of a fourth‐generation lithotripter, the Sonolith Vision (Technomed Medical Systems, Vaulx‐en‐Velin, France) for treating single previously untreated renal calculi, and to compare the results with the reference standard HM‐3 (Dornier MedTech Europe GmbH, Wessling, Germany) in the same population originally studied by the USA Cooperative Study Group in 1986. PATIENTS AND METHODS The Sonolith Vision uses an innovative electroconductive shock‐wave generator with an elliptical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 25 publications
5
21
2
Order By: Relevance
“…Therefore, electromagnetic shock wave systems were developed with variations in the focal zone, allowing the delivery of greater energy per impulse. 1,18,20 We evaluated and compared the treatment outcome in renal and ureteral stone cases with and without prior ureteral stent placement using the novel Pulso electromagnetic shock wave system integrated into the Lithoskop platform. Its large focal width allows the delivery of increased energy per impulse to the stone and low energy density to minimize adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, electromagnetic shock wave systems were developed with variations in the focal zone, allowing the delivery of greater energy per impulse. 1,18,20 We evaluated and compared the treatment outcome in renal and ureteral stone cases with and without prior ureteral stent placement using the novel Pulso electromagnetic shock wave system integrated into the Lithoskop platform. Its large focal width allows the delivery of increased energy per impulse to the stone and low energy density to minimize adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…These new generation lithotriptors have improved functionality but an inferior SFR, partly due to a smaller focal zone compared to that of the HM3. 1 Recent retrospective studies of new generation lithotriptors showed a favorable disintegration rate with further improvement in treatment safety. 2,3 Treatment success correlates with stone size.…”
mentioning
confidence: 99%
“…Failure of ESWL results in unnecessary exposure of renal parenchyma to shock waves and complications; therefore, alternative treatments are needed, incurring additional expense. 10 In our unit, these are estimated at $500 US per ESWL session. A number of stone characteristics, such as fragility, size, location and composition, are known to affect outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Tiselius published higher rates using two third-generation lithotripters, however, this study included no direct comparison to the HM3 [ 17 ]. Nomikos and co-workers presented a comparison of a fourth-generation lithotripter with the HM3: the demonstrated comparable results, but fewer analgesics were required using the fourth-generation machine [ 22 ]. In summary, evidence suggests that lithotripters of every generation can be used for treatment of ureteral stones with reasonable effi cacy.…”
Section: Technical Parametersmentioning
confidence: 73%